EMPLOYEE PERFORMANCE IMPROVEMENT THROUGH COMPENSATION AND WORK DISCIPLINE AT PT. ICHTIAR GUSTI PUDI IN LANDAK REGENCY - Pranoto, Desmi; Kurniati, Dewi; Suharyani, Anita (Jurnal AGRISEP, 2022)
Human resources are central in an institution or company. So that management activities run as desired, the company must have employees who are knowledgeable, qualified skills, and ability to manage their businesses as much as possible so that employee performance will increase. The level of success of a company can be judged based on performance. Employee performance increases if the provision of adequate compensation and good work discipline. Through this research is to analyzes the influence of compensation and discipline on employee performance at PT. Ichtiar Gusti Pudi, Landak Regency. The location of this research at Pagong Hamlet, Amboyo Inti Selatan Village, Ngabang District, Landak Regency. This study is a population study by giving a questionnaire to the entire population of 108 people consisting of maintenance employees in all parts of the company.  The data were obtained using a questionnaire with a Likert scale 1-5 scoring technique. The method of analyzing data using SEM is assisted by LISREL 8.80 software. The results show that compensation has an effect on employee performance. It appears that the t-value of the compensation variable is 3.05> 1.96. Work discipline has an effect on employee performance, with the t-value of the variable being 2.28> 1.96.